Demographic Characteristics and Reasons for Progestin Subdermal Implant (PSI) Use: Inputs for Alternative Family Planning Method - Ma. Sandra Rivera; John Mark R. Asio (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the demographic characteristics and reasons for Progestin Subdermal Implant (PSI) use among selected women in Central Luzon, Philippines. The study used descriptive-correlation research on 75 volunteer women using purposive sampling. The study observed significant differences in age, occupation, educational attainment, number of living children, type of family planning used before PSI use, reasons for practicing family planning, type of birth delivery, and plan to have another baby. Lastly, significant relationships were found in the same demographic characteristics and reason for the PSI use. The study concluded that there exists variation in the use of PSI and association for the benefit of PSI among the respondents.